Police Stress and Domestic Violence in Police Families in Baltimore, Maryland, 1997-1999 - Gershon, Robyn ([Verlag nicht ermittelbar], 2000)
This study was designed to address deficiencies in the existing literature on police work stress and especially on police stress-related domestic violence. The study sought to answer the following questions: (1) What is the relationship between police stress and domestic violence in police families? (2) What is the extent of domestic violence in police families? (3) What are the current stressors that contribute to police stress? (4) What are some of the tools available to measure or evaluate domestic violence in police families? (5) Can potentially effective interventions be identified to address the risk factors for stress-related domestic violence in police families? The study was a collaboration among the Baltimore City Fraternal Order of Police, the Baltimore Police Department, and a research team from the Johns Hopkins School of Public Health. Self-administered questionnaires were distributed to approximately 1,100 law enforcement officers who volunteered to participate in the study. Major variables focus on stressors, workplace/stress environment, coworker environment, unfair treatment, work satisfaction, administrative support, health problems, behavior problems, and psychological problems. Demographic variables include gender, age, ethnicity, education, current rank, military service, marital status, and if spouse/partner was a police officer.